How does climate exacerbate root causes of conflict in the Philippines? Climate security pathway analysis - Ferré García, Tania; Madurga Lopez, Ignacio M.; Medina, Leonardo; Carneiro, Bia; Liebig, Theresa Ines; Pacillo, Grazia; Läderach, Peter (2023)
This factsheet gives answers on how climate exacerbates root causes of conflict in the Phillipines, using a pathway analysis. Two main pathways are identified: